MENINGKATKAN PARTISIPASI INDONESIA DALAM MISI PEMELIHARAAN PERDAMAIAN PBB MELALUI INDONESIAN CIVILIAN PEACEKEEPER - Sihite, Ganda Martunas; Ichsan Malik; I Gede Sumertha KY; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Peacekeeping is a global challenge that requires active engagement from the international community. One increasingly necessary form of involvement is through the deployment of civilian peacekeepers. Indonesia, as a nation with a longstanding commitment to UN peacekeeping missions, can play a more active and significant role in providing civilian peacekeepers. This research aims to analyze the strategies and concrete steps that Indonesia can take to enhance its participation in UN peacekeeping missions through civilian peacekeepers. By reviewing past experiences and contributions, this study provides profound insights into Indonesia's potential contributions in this context. The research methodology involves analyzing Indonesia's foreign policy, case studies on civilian peacekeeper participation, and interviews with relevant stakeholders, including government representatives, non-governmental organizations, and academic figures. The research findings indicate that increasing Indonesia's participation in UN peacekeeping missions through civilian peacekeepers requires enhancing human resource capacity, strengthening inter-agency cooperation, and formulating more directed policies. The implications of these findings include recommendations for strengthening training programs, developing international cooperation agreements, and actively using diplomacy to promote Indonesia's role as a civilian peacekeeper. By exploring potential and addressing existing challenges, this research presents a comprehensive view of how Indonesia can more effectively contribute to UN peacekeeping missions through civilian peacekeepers, with the hope of strengthening Indonesia's role in maintaining global peace and security.